Spontaneous sublingual hematoma as a complication of severe hypertension: first report of a case - Prepageran, N.; Raman, R.; Ismail, S.M.; Rahman, Z.A.A. (SAGE Publications, 2002)
We describe what we believe is the first reported case of a sublingual hematoma secondary to severe hypertension. The patient, a 77-year-old woman, experienced a spontaneous hematoma of the floor of the mouth, tongue, and sublingual space that eventually caused an airway obstruction. We performed an emergency tracheostomy under local anesthesia and then evacuated the hematoma through an incision along the floor of the mouth. The patient recovered uneventfully.